A new dual-functional chemsensor for the trace detection of mercury ion and imaging of hypochloric acid. (November 2021) - Wang, Juan; Liu, Qian; Zhang, Shenghong; Fu, Guangqin; Zhang, Shilian; Lu, Yiqiong; Wu, Haixia; Zhang, Huiju; Zhou, Zhan
Abstract: Herein, a new dual-functional chemsensor 2-amino-3-((( E )-(5-(9-phenyl-9 H -carbazol-3-yl)thiophen-2-yl)methylene)amino)maleonitrile (abbreviated as FDW ) was designed and prepared for the trace detection mercury ion and imaging of hypochloric acid by two different fluorescence channels. The yellow-green channel of FDW was turned on within 6 min after adding trace-level Hg 2+ under 365 nm UV lamp irradiation. For the first time, we proved that the chelation of mercury ions with FDW weakened the binding ability of CN, making it easy to break down under UV irradiation and generate the strong fluorescent chromophores. The detection limit was calculated to be as low as 0.34 nM, which demonstrated its potential applications in actual food samples. Interestingly, upon the addition of ClO −, the blue emission of FDW was significantly increased along with color change (from pale yellow to colorless). Under optimal conditions, the calibration curve is linear in the wide concentration range (0–240 μM), and the detection limit was 107 nM. In addition, FDW was successfully used for fluorescence imaging of ClO − in RAW 246.7 cells. Highlights: Dual-functional chemsensor (FDW ) was designed and prepared. The yellow-green channel of FDW was turned on after adding trace-level Hg 2+ under 365 nm UV lamp irradiation. FDW was applied to monitor hypochloric acid in living cells through the blue channel.